Arc Length is 1/4th of the circumference .
<u>Step-by-step explanation:</u>
Here we need to find fraction of the circumference is this arc when An arc subtends a central angle measuring
radians ! Let's find out :
We know that circumference of an arc subtending a central angle of x is :
⇒ 
⇒ 
⇒ 
⇒ 
⇒ 
⇒ 
Therefore , Arc Length is 1/4th of the circumference .
Answer:
Step-by-step explanation:
3 sqrt2
Answer is (D). -6-7x. Or to play with it a lil bit -7x-6. The numbers and coefficients and signs are all correct doesn’t matter how you form them unless “they” disagree with it
Answer:
113.1
Step-by-step explanation:
My work:
<span>Simplifying
(4x3 + 7y3z4)(4x3 + 7y3z4) = 0
Multiply (4x3 + 7y3z4) * (4x3 + 7y3z4)
(4x3 * (4x3 + 7y3z4) + 7y3z4 * (4x3 + 7y3z4)) = 0
((4x3 * 4x3 + 7y3z4 * 4x3) + 7y3z4 * (4x3 + 7y3z4)) = 0
Reorder the terms:
((28x3y3z4 + 16x6) + 7y3z4 * (4x3 + 7y3z4)) = 0
((28x3y3z4 + 16x6) + 7y3z4 * (4x3 + 7y3z4)) = 0
(28x3y3z4 + 16x6 + (4x3 * 7y3z4 + 7y3z4 * 7y3z4)) = 0
(28x3y3z4 + 16x6 + (28x3y3z4 + 49y6z8)) = 0
Reorder the terms:
(28x3y3z4 + 28x3y3z4 + 16x6 + 49y6z8) = 0
Combine like terms: 28x3y3z4 + 28x3y3z4 = 56x3y3z4
(56x3y3z4 + 16x6 + 49y6z8) = 0
Solving
56x3y3z4 + 16x6 + 49y6z8 = 0
Solving for variable 'x'.
Factor a trinomial.
(4x3 + 7y3z4)(4x3 + 7y3z4) = 0
Subproblem 1Set the factor '(4x3 + 7y3z4)' equal to zero and attempt to solve:
Simplifying
4x3 + 7y3z4 = 0
Solving
4x3 + 7y3z4 = 0
Move all terms containing x to the left, all other terms to the right.
Add '-7y3z4' to each side of the equation.
4x3 + 7y3z4 + -7y3z4 = 0 + -7y3z4
Combine like terms: 7y3z4 + -7y3z4 = 0
4x3 + 0 = 0 + -7y3z4
4x3 = 0 + -7y3z4
Remove the zero:
4x3 = -7y3z4
Divide each side by '4'.
x3 = -1.75y3z4
Simplifying
x3 = -1.75y3z4
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(4x3 + 7y3z4)' equal to zero and attempt to solve:
Simplifying
4x3 + 7y3z4 = 0
Solving
4x3 + 7y3z4 = 0
Move all terms containing x to the left, all other terms to the right.
Add '-7y3z4' to each side of the equation.
4x3 + 7y3z4 + -7y3z4 = 0 + -7y3z4
Combine like terms: 7y3z4 + -7y3z4 = 0
4x3 + 0 = 0 + -7y3z4
4x3 = 0 + -7y3z4
Remove the zero:
4x3 = -7y3z4
Divide each side by '4'.
x3 = -1.75y3z4
Simplifying
x3 = -1.75y3z4
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.
Hope that this help you! =)</span>